High Crystal Number Densities From Mechanical Damage - Lindoo, Amanda; Cashman, Katharine V. (Frontiers in Earth Science, 2021)
Laboratory experiments investigating syn-eruptive crystallization are fundamental for interpreting crystal and vesicle textures in pyroclasts. Previous experiments have advanced our understanding by varying decompression and cooling pathways, volatile components, and melt composition. However, they have largely failed to produce the high crystal number densities seen in many cryptodome and dome samples. In this study, we approach the problem by exploring non-linear decompression pathways. We present two series of experiments: (1) decompression from low initial starting pressure and (2) a compression-and-release step after the initial decompression. The purpose of each series was to simulate (1) decompression of magma that stalls during ascent and (2) pressure cycling that occurs in non-erupted magma that is decompressed in the conduit during episodic explosive activity. The experiments were carried out on a synthetic rhyodacite (SiO2 = 69 wt. %) held initially at 50 MPa and 885oC then decompressed at rates of 0.026-0.05 MPa s-1 to 10 MPa. A subset of experiments was then subjected to a compression step to 110 MPa followed by near-instantaneous release back to 10 MPa. A substantial volume fraction of dendritic microlites formed during the initial hold at 50 MPa; additional crystallization during subsequent decompression to ≥10 MPa was minimal, as evidenced by only small increases in crystallinity and comparable crystal number densities. Samples that underwent recompression followed by a second decompression showed no increase in crystal volume fraction but did show extensive disruption of the initial dendritic, box-work microlite structures that produced high number densities of small individual crystals. The disruption was driven by a combination of rapid vesiculation, expansion and resulting shear along the capsule walls. From these results, we suggest that high crystal number densities may be a signature of rapid deformation occurring after magma stalling in the subsurface, perhaps related to pressure cycling and accompanying rapid changes in vesicularity during repeated small and shallow-sourced explosions. We compare our experiments to pyroclasts from shallow intrusions that preceded the May 18 1980 of Mount St Helens (erupted both before and during the eruption) to illustrate the significance of our results.